Effects of altitude training on changes in hemoglobin mass, Vo2max and body composition in elite endurance athletes; impact of increased antioxidant-rich food intake on the adaptation response - Koivisto, A.; Paulsen, G.; Bohn, S. K.; Garthe, I.; Paur, I.; Tonnesen, E.; Raastad, T.; Blomhoff, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Training at high altitude increases the production of reactive oxygen and nitrogen species (RONS), which potentially induce cellular damage. As a countermeasure, athletes are recommended to increase antioxidant intake. However, RONS are important cellular signalling molecules, and high-dose single-antioxidant supplement intake may blunt responses to endurance training. Whether increased consumption of antioxidant-rich foods will affect training adaptations in a similar manner, is currently unknown. Thus, this study aimed to assess the effects of training at moderate altitude in elite endurance athletes and evaluate the impact of antioxidant rich foods on the adaptation response. METHODS: Thirty-one national team endurance athletes (8 females, 23 males) were randomly assigned to antioxidant rich snack (AO, n=16) or placebo group (PL, n=15). During a 3-week training camp at moderate altitude (2340 m) athletes received daily eucaloric AO (smoothies, nuts, dried berries/fruit, dark chocolate) or PL snacks. Before and after the altitude camp hemoglobin mass (Hbmass), blood volume (BV), lean body mass (LBM) and fat mass (FM) were determined and fasting blood samples collected and analyzed for hemoglobin (hb), hematocrit, erythrocytes and ferritin. Additionally, VO2max (treadmill) was assessed in 16 athletes (AO, n=10, PL, N=6). RESULTS: Moderate altitude training induced increases in Hbmass (4.9 %, p<0.001), hematocrit (4.0 %, p=0.001), erythrocytes (5.0 %, p<0.001), and VO2max (2.6 %, p<0.01), whereas S-ferritin was reduced (-16.5 %, p=0.001). Body mass, LBM, and FM remained unchanged. No significant differences were found between groups for any of the adaptation response parameters. Compliance in AO group was 95%. DISCUSSION: Three-weeks of training at moderate altitude increased Hbmass and VO2max, important physiological determinants for endurance performance in elite athletes. Increased consumption of antioxidant-rich foods (doubling AO intake) was well tolerated by the athletes and did not interfere with the adaptive responses to altitude training. Whether high intake of antioxidants from food modulated systemic redox balance and inflammation markers awaits further analyses.